Mapping the effect of antimicrobial resistance in poultry production in Senegal: an integrated system dynamics and network analysis approach - Joshua Aboah; Joshua Aboah; Babacar Ngom; Eves Emes; Awa Gueye Fall; Moutar Seydi; Ardiouma Faye; Michel Dione (Frontiers in Veterinary Science, 2023)
The impact of antimicrobial resistance (AMR) extends beyond the farm-level to other stakeholders warranting the need for a collaborative approach to combat AMR while optimising production objectives and safeguarding human health. This study maps out the effect of AMR originating from poultry production in Senegal and highlights the entry points for interventions from stakeholders’ perspectives. A causal loop diagram (CLD) was developed following a group model building procedure with 20 stakeholders and integrated with network analysis by translating the CLD into an unweighted directed network. Results indicate that with an eigenvector centrality of 1, 0.85, and 0.74, the production cost, on-farm profit, and on-farm productivity, respectively are the most ranked influential variables driving the complexity of AMR in the poultry production system. Two reinforcing feedback loops highlight the dual benefits of improving on-farm productivity and increasing on-farm profit. However, one balancing feedback loop that revolves around the causal link between producers’ investment in qualified human resource personnel to ensure good farm management practices underline the financial implication of producers’ investment decisions. The findings provide precursory groundings for the development of a quantitative SD model, the formulation of intervention scenarios and ex-ante impact assessment of the cost-effectiveness of the interventions.